Knowledge, attitude and practices regarding World Health Organization surgical safety checklist and the challenges in its implementation at a teaching hospital in North India - Sharma, Priya; Tripathi, Vartika; Gupta, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The WHO in 2009 published the surgical safety checklist (SSC) for reducing the surgical complications. For its successful implementation it is imperative to identify the current knowledge, attitude and practices of the involved personnel and explore the anticipated barriers. Objective of this study was to evaluate the knowledge, attitude and practices of the participants about the SSC and determine the possible challenges in its implementation. Methods: This study is a descriptive, cross-sectional study involving the use of a pre-tested questionnaire carried out in a teaching hospital. All personnel involved in the operation theater who gave their written consent were enrolled. Results: Awareness regarding the SSC is high and existing practices are favorable towards patient safety amongst Hospital personnel. Attempts should be made to educate all personnel to gain complete knowledge regarding the checklist. The anticipated barriers, of which lack of knowledge was found to be the most prominent, should be dealt with. Conclusions: A strategy aimed at proper education, stepwise implementation, alleviating the hindrances and regular feedbacks can result in decreasing the surgery related complications and morbidities through implementation of the surgical safety checklist.